The Effectiveness of Olive Oil to Combat Lice in Pregnant Women and Children - Bafreen Mohamad Raza; Haifaa Mohammed Amin; Hanadi Abdul-Elah Abdul-Razzaq (Indian Journal of Forensic Medicine & Toxicology, 2021)
For the period from February 2019 until August 2019 it was checked 75 cases of pregnant women andchildren included girls and boys, and 28 pregnant women, 42 girls and 5 males were found to be infected. Head louse , as the study showed that the highest incidence of head louse was recorded among girls , itreached 56% , followed by pregnant women with a percentage of infection 37.33% , while males recordedless infection with head louse amounted to 6.66% , respectively , and olive oil was used to determine itseffectiveness to combat head louse as a natural substance , and it used Statistical analysis was used Dunkintest .